2013
DOI: 10.33225/jbse/13.12.716
|View full text |Cite
|
Sign up to set email alerts
|

Success and Failure in Science Education: A Focus Group Study on Turkish Students

Abstract: This study aims to investigate primary school students' success and failure in science courses. The participants of the study included 24 students enrolled in the 8th grade of a secondary school and focus group interviews were held. It was observed in the study that the successful students focused more on science and mathematics classes, while the unsuccessful students did more on verbal classes. Considering the topics the successful group considered related to the science class, the students in the successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 37 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Especially in academic settings, the attribution of success and failure to internal or external factors can influence students' continued involvement in science (Assouline et al, 2006; Guler, 2013; Simpson & Maltese, 2017). Moreover, in the context of the German Physics Olympiad, Treiber (2020) found that participants hold different views about whether or not their results depended on their own effort in the competition–especially in the first competition round.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in academic settings, the attribution of success and failure to internal or external factors can influence students' continued involvement in science (Assouline et al, 2006; Guler, 2013; Simpson & Maltese, 2017). Moreover, in the context of the German Physics Olympiad, Treiber (2020) found that participants hold different views about whether or not their results depended on their own effort in the competition–especially in the first competition round.…”
Section: Introductionmentioning
confidence: 99%